S100B AS A SEROLOGIC MARKER FOR COGNITIVE DYSFUNCTION FOLLOWING OPEN-HEART SURGERY - BAKTIAR, YOSHUA; SOENARTO, RATNA FARIDA; ALATAS, ANAS; AUERKARI, AINO NINDYA (International Journal of Applied Pharmaceutics, 2020)
Objective: Postoperative cognitive dysfunction (POCD) can feature a wide spectrum of clinical symptoms, from asymptomatic to debilitating dementia, that lead to increased dependence, lower quality of life, morbidity, and mortality. Protein S100B is a direct marker for neuronal cell damage. We aimed to evaluate S100B as a biomarker for predicting POCD following open-heart surgery. Methods: This was an observational-analytic study to assess changes of the S100B level following open-heart surgery in Cipto Mangunkusumo Hospital, Jakarta. All subjects underwent cognitive function evaluations that consisted of six psychometric tests on the day prior to surgery and five days after surgery. Cognitive dysfunction was determined if there was a>20% cognitive score drop from baseline values in at least two tests. Blood samples for S100B were obtained (1) before the induction of anesthesia and (2) six hours after surgery. Samples were analyzed using enzyme-linked immunosorbent assay for S100B. All data were analyzed using SPSS 20. Results: Among the 55 subjects analyzed, 31 (56.4%) were found to have a decline in cognitive function. There were no differences in baseline characteristics, comorbidities, and perioperative data. Oxygen contents also did not show significant differences at any time. The S100B levels in all subjects increased. This increase was>1.5x higher in subjects with POCD compared to those without POCD (2.15[0.22–60.03] vs. 1.33[0.15–19.77] ng/ml, p = 0.16). However, this difference was not statistically significant. Conclusion: This study showed that serum S100B is higher in POCD patients and has the potential to be a biomarker for predicting POCD after open-heart surgery.